Pterichis avicula (Orchidaceae), a new species from Peru - Kolanowska, Marta (Phytotaxa, 2025)
Pterichis avicula is described based on Peruvian material. The morphological characteristic of the species is provided together with an illustration of its floral segments and comparison with similar orchids. This new species resembles the Ecuadorian P. tunguraguona and P. seleniglossa in the lip form which is lunate-reniform above a truncate base. Pterichis avicula is easily distinguished from the former by the shape of the petals and the proportionally larger lip middle lobe. Unlike the new species, P. seleniglossa has ovate, small lip middle lobe which constitutes less than half of the total lip length and the sinus between the lobes in this species is indistinctive.